Iatrogenic Colon Perforation Due to Colonoscopy Presenting as a Diffuse Subcutaneous Emphysema - Can, Ömer Faruk; Bozdağ, Ahmet (My University, 2020)
Colonoscopy is a procedure frequently used for the screening, diagnosis and treatment of colorectal diseases. While colonoscopy is generallyaccepted as a safe procedure, it may lead to morbidity and mortality with serious complications such a colon perforation. This risk is higher wheninterventional procedures are applied. After colon perforation, extracolonic gas can pass into embryologically relevant body compartments. Free airdue to perforation has been reported in the thorax, mediastinum, neck, scrotum and lower extremities. Herein, we present a patient who presentedwith diffuse subcutaneous emphysema after a colonoscopic procedure to investigate the aetiology of anaemia.
Keywords: Genel ve Dahili Tıp; Patoloji